Post-selenylation defect passivation method based on thin-film solar cell

Selenium antimony sulfide thin film was prepared by post-selenization and hydrothermal deposition by selenium in octene solution, which solved the problems of low efficiency of selenium antimony sulfide solar cells and easy oxidation of films, and achieved high efficiency and stable selenium antimony sulfide solar cells.

CN119562626APending Publication Date: 2025-03-04TIANJIN POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311100021.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing antimony sulfide solar cells have low efficiency, and their defects have an impact on battery performance. The thin film of antimony sulfide in selenium is prone to oxidation, affecting battery stability.

Method used

Selenium dissolved in octene solution was used for post-selenization treatment, and a thin film of antimony selenium sulfide was prepared by hydrothermal deposition, and a carbon electrode was used to prevent oxidation during the annealing process.

Benefits of technology

The crystallinity and grain size of the selenium antimony sulfide film are improved, the morphology and energy level orientation of the film are improved, the photoelectric conversion efficiency is significantly improved, and the film is effectively prevented.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119562626A_ABST
    Figure CN119562626A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a thin-film solar cell from cadmium sulfide based on a post-selenylation and hydrothermal deposition method. The morphology of the cadmium sulfide thin film can be improved by preparing cadmium sulfide through the hydrothermal deposition method, and the cadmium sulfide thin film prepared through the hydrothermal deposition method is compact in morphology, clean and transparent. The crystallinity of the selenium antimony sulfide thin film subjected to post-selenylation is improved, and defects are reduced. The thin-film solar cell comprises a conductive substrate (including FTO and the like), an electron transport layer (CdS), a selenium antimony sulfide (Sb2 (S, Se) 3 for short) absorption layer, a hole transport layer and a metal counter electrode. The morphology of the cadmium sulfide thin film is improved, the morphology is improved through the selenium selenide antimony sulfide thin film, the energy level orientation is good, the deep energy level defect is reduced, and the efficiency of the thin film solar cell can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of antimony selenide sulfide solar cells, and in particular relates to a method for enhancing the efficiency of antimony selenide sulfide solar cells through a new post-selenization strategy. Background Art

[0002] In recent years, energy crisis and environmental issues are receiving more and more attention, because the large-scale consumption of non-renewable energy and environmental pollution have brought great threats to the global society. With the blind development of non-renewable energy, resources have begun to deplete, and people have begun to seek a green resource to achieve sustainable development of the environment. Solar energy is a clean and renewable energy source that has attracted much attention. A crucial link in photovoltaic power generation technology is solar photovoltaic cells, which can be divided into three generations according to their absorption layer materials. The first generation is silicon-based solar cells, the second generation is thin-film solar cells, and the third generation is new concept solar cells, including high-concentration solar cells, organic solar cells, flexible solar cells and dye-sensitized nano solar cells. Among them, except for high-concentration solar cells, which have begun to be applied on a small scale, other technologies are still in the laboratory stage. At present, silicon-based solar cells still occupy a major position in the market. Thin-film solar cells have become an important form and research hotspot of photovoltaic power generation due to their advantages such as low raw material consumption and flexible rollability. The conversion efficiency of copper indium gallium selenide and cadmium telluride thin-film solar cells has exceeded 22%, and has been industrialized. The efficiency of perovskite thin-film solar cells in the laboratory is comparable to that of crystalline silicon solar cells. For example, the conversion efficiency of perovskite stacked thin-film solar cells has reached 24.9%. However, since indium and gallium in copper indium gallium selenide thin films are rare elements, cadmium in cadmium telluride thin films is highly toxic, and the stability of perovskite thin film materials still needs to be improved. These factors have limited the further development of thin-film solar cells to a certain extent. Therefore, finding or developing a light-absorbing layer thin film material with abundant raw materials, non-toxicity, simple preparation methods and stability is the key to promoting the development of thin-film solar cells.

[0003] Recently, various sulfide materials have attracted widespread attention in the field of new energy, such as copper zinc tin sulfide (CZTS), iron disulfide (FeS2), stannous sulfide (SnS), copper antimony sulfide (CuSbS2), cuprous oxide (Cu2O) and antimony selenide sulfide Sb2(S1-x, Sex)3(0≤x≤1). Among them, antimony selenide sulfide is a raw material with excellent photoelectric properties and abundant reserves, so it has attracted much attention. Antimony selenide sulfide Sb2(S1-x, Sex)3(0≤x≤1) is a semiconductor material that can be regarded as a binary or quasi-binary compound. The energy band adjustment range of this material is 1.1-1.8eV, and the light absorption coefficient can reach up to 105cm -1 , good chemical stability, not easily affected by water and air, abundant raw material resources, easy to prepare, can achieve wide-band response, low toxicity. Therefore, it has become a hot topic of research recently. In 1950, Sb2Se3 was synthesized, and it was confirmed that Sb2Se3 and Sb2S3 had the same structure. In 1957, TIdeswell confirmed that the characteristics of the two compounds were similar. In 2005, Rodriguez-Lazcano et al. obtained a polycrystalline Sb2Se3 film by chemical bath deposition, and then heated the film in selenium vapor at 573K to enrich the selenium in the film. In 2016, Professor Liu Meng's research group used the hydrothermal method to obtain a thin film of Sb2S3 for the first time. In 2021, Jesús Capistrán-Martínez et al. placed antimony sulfide silver in thermal contact with Se powder for post-selenization treatment, and formed a selenized film with a reduced band gap and increased photocurrent density. The great prospects of antimony selenide have attracted the attention of many scholars at home and abroad. At present, the highest known photoelectric conversion efficiency (PCE) of antimony selenide sulfide photovoltaic devices was completed by Chen Tao's team, which has exceeded 10%. Past experience in developing well-developed photovoltaic technologies has shown that defect passivation of light-absorbing materials is an effective method to optimize their crystallinity and electrical properties. Each absorber material requires a different defect passivation process to control grain growth and passivate defects. Defect passivation is the most common method to improve film crystallinity, passivate Se vacancies, and inhibit recombination losses. Therefore, determining the appropriate defect passivation treatment is of great significance for the future development of high-efficiency Sb2(S,Se)3 thin-film solar cells.

[0004] This paper mainly studies the method of using selenium dissolved in octadecene solution and then used for post-selenization to improve the efficiency of antimony selenide sulfide solar cells. First, appropriate raw materials and solvents are selected, and potassium antimony tartrate hemihydrate, sodium thiosulfate pentahydrate and sodium selenite sulfite are used as precursor materials for Sb, S and Se, and antimony selenide sulfide films are prepared by hydrothermal deposition. Selenium is dissolved in octadecene solution to form a precursor solution, and the precursor solution is spin-coated on the antimony selenide sulfide film and then annealed for post-selenization. The effects of post-selenization treatment on the film morphology, crystal structure, composition, band gap, energy level position and defects are studied. Under post-selenization conditions, the film crystallinity is improved, the grain size is enlarged, the morphology of the antimony selenide sulfide film is improved, the energy level orientation is good, and the photoelectric conversion efficiency is significantly improved compared with the control group without post-selenization, and no other impurities are introduced into the final absorption layer film. Summary of the invention

[0005] In order to solve the influence of defects on the efficiency of antimony selenide sulfide cells, the present invention uses a method of dissolving selenium in an octadecene solution and then using it for post-selenization to solve the efficiency problem of antimony selenide sulfide solar cells. Selenium vacancy defect passivation can improve the crystallinity of the film, passivate selenium vacancies, and inhibit composite losses. In addition, a new annealing method, firstly applying an electrode to the antimony selenide sulfide film and then performing a post-annealing operation, can effectively solve the oxidation problem of the antimony selenium sulfide film.

[0006] The first object of the present invention is to obtain a post-selenization method that is very suitable for antimony selenide sulfide solar cells.

[0007] The second purpose of the present invention is to prepare cadmium sulfide by a hydrothermal deposition method so as to improve the morphology of the cadmium sulfide film.

[0008] The third purpose of the present invention is to obtain a new annealing method that can effectively solve the oxidation problem of antimony selenide sulfide film.

[0009] The fourth object of the present invention is to obtain a photovoltaic device based on post-selenization and hydrothermal deposition method to prepare cadmium sulfide, making it very suitable for solar cells.

[0010] In a first aspect of the present invention, a post-selenization method is provided for a method for preparing an antimony selenide sulfide solar cell, the steps of which include:

[0011] (1) Cleaning of three-necked round-bottom flask, construction of condensation reflux device and nitrogen pipeline;

[0012] (2) Weighing selenium powder and octadecene solution, placing them in a three-necked round-bottom flask with a stirrer, and adding a certain amount of ultrapure water;

[0013] (3) Place a three-necked round-bottom flask on a magnetic stirring heating mantle and connect it to a condensing reflux device and a nitrogen pipeline;

[0014] (4) setting the magnetic stirring heating mantle to an appropriate stirring speed, heating, introducing nitrogen, and carrying out the reaction under nitrogen protection;

[0015] (5) After the reaction in step (4) is completed, the transparent solution is transferred to a star-shaped bottle and sealed to store in a dark place;

[0016] (6) Filtering the solution after the growth in step (5) to obtain a post-selenization selenium source.

[0017] (7) Spin-coat the post-selenide selenium source obtained in step (6) onto the surface of the antimony selenide sulfide film at a rotation speed (3000 rpm / 30 s), and then heat-treat the film at 350°C in a nitrogen-filled glove box for 10 min.

[0018] In a second aspect of the present invention, the morphology of the cadmium sulfide film can be improved by preparing cadmium sulfide by a hydrothermal deposition method, and the steps include:

[0019] (1) Place ammonia water and cadmium nitrate tetrahydrate in a beaker and stir until completely dissolved.

[0020] (2) Add thiourea, dissolve it in deionized water and stir to fully dissolve it, and the precursor solution is prepared;

[0021] (3) Place the FTO conductive glass in a 50 mL hydrothermal reaction kettle, and pour in the precursor solution in (2) for hydrothermal treatment. After the hydrothermal treatment is completed, take out the hydrothermal kettle and cool it to room temperature.

[0022] (4) taking out the FTO conductive glass with the thin film deposited thereon, and washing the deposited thin film with deionized water and anhydrous ethanol in turn;

[0023] (5) Dry with nitrogen and anneal at 100°C for 10 min;

[0024] (6) Spin coating a methanol solution containing cadmium chloride on the surface of the cadmium sulfide, and annealing on a hot plate at 400° C. for 10 min after the spin coating.

[0025] The third object of the present invention is to provide a new annealing method that can effectively solve the oxidation problem of antimony selenide sulfide film, and the steps are as follows:

[0026] (1) The antimony selenide sulfide film prepared hydrothermally is first coated with a carbon electrode;

[0027] (2) The film coated with carbon electrode was annealed at 350 °C in a glove box;

[0028] (3) The annealed film can effectively prevent oxidation

[0029] A fourth aspect of the present invention provides a photovoltaic device for preparing cadmium sulfide based on a post-selenization and hydrothermal deposition method, the device comprising:

[0030] substrate;

[0031] Electron transport layer;

[0032] Antimony selenide sulfide solar cell (abbreviated as Sb2(S,Se)3) absorption layer;

[0033] hole transport layer;

[0034] Metal counter electrode.

[0035] Base The substrate of the present invention is not specifically limited, as long as it does not limit the purpose of the present invention. It can be conductive glass, conductive metal, etc. Preferably, FTO glass is used.

[0036] Electron transport layer : The electron transport layer of the present invention uses cadmium sulfide prepared by a hydrothermal deposition method.

[0037] Sb2(S,Se)3 absorption layer There is no specific limitation on the material of the antimony selenide light absorbing layer. After the light absorbing layer material is prepared, it is post-selenized using the selenium source invented above.

[0038] Hole transport layer: The hole transport layer is not particularly limited as long as it does not limit the purpose of the present invention. (eg, Spiro-OMeTAD, etc.)

[0039] Metal Counter Electrode The counter electrode (or back electrode) of the present invention is not specifically limited, as long as it does not limit the purpose of the present invention. Aluminum paste, gold, carbon, etc. can be selected. Preferably, a gold electrode is selected. Preferably, the thickness of the counter electrode is 100 nm.

[0040] Compared with the prior art, the present invention has the following advantages and positive effects:

[0041] (1) The present invention provides a photovoltaic device for preparing cadmium sulfide based on post-selenization and hydrothermal deposition methods, which can improve the efficiency of antimony selenide sulfide photovoltaic devices;

[0042] (2) The cadmium sulfide film prepared by the hydrothermal deposition method has a dense, clean and transparent morphology;

[0043] (3) The crystallinity of the post-selenized antimony selenide sulfide film is improved, the grain size is enlarged, the morphology of the antimony selenide sulfide film is improved, and the energy level orientation is good;

[0044] (4) The light absorbing layer material selected by the present invention has excellent light absorption, good chemical stability, is not easily affected by water and air, etc., has abundant raw material resources, is easy to prepare, can achieve wide-band response, and has low toxicity;

[0045] (5) The method of the present invention is simple, low-cost and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings, wherein:

[0047] Figure 1 is a schematic diagram of post-selenization optimized antimony selenide sulfide solar cell; DETAILED DESCRIPTION

[0048] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out under normal conditions. Unless otherwise defined or specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention.

[0049] Example 1: Preparation of spherical CdSe nanomaterials using the present invention

[0050] (1) Add Se powder to a three-necked flask, then add octadecene solvent, and heat it in a heating mantle. Stir continuously during the heating process. At this time, the Se powder dissolves in the octadecene solvent to form an orange transparent solution.

[0051] (2) Cd(Ac)2 and oleic acid were added to a 25 ml beaker, and the beaker was placed in an oven at 120°C for 0.5 hours, during which time Cd(Ac)2 dissolved in the oleic acid to form cadmium oleate and obtain a clear liquid.

[0052] (3) Then the solution in the beaker of step (2) is quickly added to the three-necked flask containing the Se raw material in step (1), and the reaction temperature is controlled by the heating voltage of the heating jacket. Stirring is maintained during the reaction.

[0053] (4) After reacting for 45 minutes, the reaction solution was cooled and 20 ml of ethanol was added to precipitate the CdSe nanocrystals, followed by centrifugal analysis.

[0054] (5) Then dissolve the precipitate in n-hexane solution.

[0055] Example 2: Preparation of antimony selenium sulfide solar cells using the present invention

[0056] (1) The FTO conductive glass was ultrasonically cleaned with deionized water, acetone, isopropanol, and anhydrous ethanol for 40 minutes each, dried with nitrogen, and then cleaned in the chamber of an oxygen plasma cleaning instrument for 15 minutes to obtain a clean and dry FTO.

[0057] (2) Measure the cadmium nitrate solution and ammonia solution, pour them into a beaker in turn, and stir for 150 seconds. Then add the thiourea solution, stir for 30 seconds, then add 70 ml of ultrapure water, and continue stirring for 30 seconds to prepare a precursor solution.

[0058] (3) Place the FTO obtained in step (1) into the inner container of an autoclave and pour in the precursor solution prepared in step (2).

[0059] (4) Place the hydrothermal kettle sealed in step (3) into the supply box. Set the oven temperature to 70°C, the heating time to 10 min, react at 70°C for 40 min, then take out the hydrothermal kettle and cool naturally to room temperature.

[0060] (5) The film deposited in step (4) was rinsed with ultrapure water and anhydrous ethanol in turn, dried with nitrogen, and heated on a 100° C. hot plate for 10 min. After cooling, a methanol solution containing cadmium chloride was spin-coated on the surface of the cadmium sulfide, and then annealed on a 400° C. hot plate in air for 10 min.

[0061] (6) Weigh potassium antimony tartrate hemihydrate and sodium thiosulfate pentahydrate and dissolve them in 40 ml of ultrapure water, stir them thoroughly to completely dissolve. After the mixed solution in the cup is fully stirred, add the sodium thiosulfate solution and stir for 1 min to complete the preparation of the precursor solution;

[0062] (7) Place the FTO obtained in step (5) into the inner container of an autoclave and pour in the precursor solution prepared in step (2).

[0063] (8) Place the hydrothermal kettle sealed in step (3) into the supply box. Set the oven temperature to 120°C, the heating time to 13 min, react at 120°C for 3 h, then take out the hydrothermal kettle and cool naturally to room temperature.

[0064] (9) After the hydrothermal process is completed, the deposited precursor film is taken out, rinsed with ultrapure water and anhydrous ethanol in turn, and dried with nitrogen. In a nitrogen atmosphere, the precursor film is placed on a heating plate and heat treated at 100°C for 2 minutes.

[0065] (10) The post-selenization selenium source prepared in the present invention was spin-coated on the surface of the antimony selenide sulfide film in step (9) (3000 rpm / 30 s), and then the film was placed in a nitrogen-filled glove box and heat treated at 350° C. for 10 min.

[0066] (11) After cooling, a back electrode (gold or silver, etc.) is prepared on top of the hole transport layer by vacuum coating.

[0067] (12) After cooling, continue annealing on a hot plate at 350°C for 10 min.

[0068] (13) Encapsulate solar cells according to standard processes.

[0069] Example 3: Preparation of CdTe thin film battery using the present invention

[0070] (1) The FTO conductive glass was ultrasonically cleaned with deionized water, acetone, isopropanol, and anhydrous ethanol for 40 minutes each, dried with nitrogen, and then cleaned in the chamber of an oxygen plasma cleaning instrument for 15 minutes to obtain a clean and dry FTO.

[0071] (2) Measure the cadmium nitrate solution and ammonia solution, pour them into a beaker in turn, and stir for 150 seconds. Then add the thiourea solution, stir for 30 seconds, then add 70 ml of ultrapure water, and continue stirring for 30 seconds to prepare a precursor solution.

[0072] (3) Place the FTO obtained in step (1) into the inner container of an autoclave and pour in the precursor solution prepared in step (2).

[0073] (4) Place the hydrothermal kettle sealed in step (3) into the supply box. Set the oven temperature to 70°C, the heating time to 10 min, react at 70°C for 40 min, then take out the hydrothermal kettle and cool naturally to room temperature.

[0074] (5) The film deposited in step (4) was rinsed with ultrapure water and anhydrous ethanol in turn, dried with nitrogen, and heated on a 100° C. hot plate for 10 min. After cooling, a methanol solution containing cadmium chloride was spin-coated on the surface of the cadmium sulfide, and then annealed on a 400° C. hot plate in air for 10 min.

[0075] (6) The CdTe absorption layer is prepared by a close-space sublimation method, the deposition temperature is about 600°C, and the total thickness of the deposited CdTe gradient absorption layer is about 3 to 5 μm.

[0076] (7) The post-selenide selenium source prepared in the present invention is spin-coated on the surface of the CdTe film in step (6) (3000 rpm / 30 s), and then the film is placed in a nitrogen-filled glove box and heat-treated at 350° C. for 10 min to form a CdTeSe / CdTe gradient absorption layer.

[0077] (8) Different from the traditional CdTe structure battery, the activation process of the CdTeSe / CdTe gradient absorption layer structure after post-selenization needs to take into account both the defect passivation process and the gradient diffusion process of Se. The activation intensity is critical to the gradient component distribution and gradient band structure of the absorption layer.

[0078] (9) The surface etching method used is bromine etching, which aims to remove the high-resistance oxide present on the surface of the prepared CdTe.

[0079] (10) High work function ZnTe:Cu is used as the back contact buffer layer structure with a thickness of about 50nm.

[0080] (11) Au is then deposited as the back contact electrode, and continuous heat treatment is performed to prepare a complete CdTe solar cell device.

[0081] Example 4: Preparation of copper indium gallium selenide thin film solar cells using the present invention

[0082] (1) The FTO conductive glass was ultrasonically cleaned with deionized water, acetone, isopropanol, and anhydrous ethanol for 40 minutes each, dried with nitrogen, and then cleaned in an oxygen plasma cleaning instrument chamber for 15 minutes to obtain clean and dry FTO.

[0083] (2) Measure the cadmium nitrate solution and ammonia solution, pour them into a beaker in turn, and stir for 150 seconds. Then add the thiourea solution, stir for 30 seconds, then add 70 ml of ultrapure water, and continue stirring for 30 seconds to prepare a precursor solution.

[0084] (3) Place the FTO obtained in step (1) into the inner container of an autoclave and pour in the precursor solution prepared in step (2).

[0085] (4) Place the hydrothermal kettle sealed in step (3) into the supply box. Set the oven temperature to 70°C, the heating time to 10 min, react at 70°C for 40 min, then take out the hydrothermal kettle and cool naturally to room temperature.

[0086] (5) The film deposited in step (4) was rinsed with ultrapure water and anhydrous ethanol in turn, dried with nitrogen, and heated on a 100° C. hot plate for 10 min. After cooling, a methanol solution containing cadmium chloride was spin-coated on the surface of the cadmium sulfide, and then annealed on a 400° C. hot plate in air for 10 min.

[0087] (6) Selecting a target material according to the conditions, DC magnetron sputtering copper indium gallium (CIG) is used to prepare a prefabricated metal film, and magnetron sputtering is used to prepare a metal prefabricated layer on the surface of cadmium sulfide in step (5).

[0088] (7) The post-selenization selenium source prepared in the present invention is spin-coated on the surface of the CIG film in step (6) (3000 rpm / 30 s), and then the film is placed in a nitrogen-filled glove box and heat-treated at 350° C. for 10 min to selenize the prefabricated metal film prepared previously.

[0089] (8) After cooling, a back electrode (gold or silver, etc.) is prepared on top of the hole transport layer by vacuum coating.

[0090] (9) After cooling, annealing was continued on a hot plate at 350°C for 10 min.

[0091] (10) Encapsulate solar cells according to standard processes.

Claims

1. A photovoltaic device for preparing cadmium sulfide based on post-selenization and hydrothermal deposition method, characterized in that: The battery structure comprises: Micro-nano functional materials arranged on the conductive surface of the substrate; substrate; Electron transport layer; Antimony selenide sulfide solar cell (abbreviated as Sb2(S,Se)3) absorption layer; hole transport layer; Metal counter electrode.

2. The electron transport layer as claimed in claim 1 is made of cadmium sulfide (CdS).

3. A method for preparing a photovoltaic device by preparing cadmium sulfide on the conductive surface of a FTO substrate based on post-selenization and hydrothermal deposition methods, characterized in that: The steps include: (1) Cleaning of substrate materials; (2) Preparation of electron transport layer by hydrothermal deposition method; (3) completing the preparation of antimony selenide sulfide precursor solution; (4) fixing the substrate in a closed container containing a precursor solution; (5) placing the sealed container of step (4) in a constant temperature device and growing for a specific time; (6) After the growth in step (5) is completed, the substrate is taken out and cleaned to obtain a photovoltaic device.

4. Step (2) as claimed in claim 3, characterized in that: The hydrothermal deposition temperature is 70°C, the hydrothermal deposition time is 40 min, the thickness of the electron transport layer is about 100 nm, and the annealing temperature of the electron transport layer is about 450°C.

5. Step (3) as claimed in claim 3, characterized in that: Preferably, the precursor solution is a mixture of potassium antimony tartrate hemihydrate and sodium thiosulfate pentahydrate.

6. The main preparation process of antimony selenide sulfide solar cells is: (1) preparing cadmium sulfide by a hydrothermal deposition method on the conductive surface of the substrate prepared as claimed in claim 3; (2) preparing an antimony selenide sulfide light absorbing layer on the electron transport layer; (3) preparing a hole transport layer; (4) Prepare a metal counter electrode.

7. The method of post-selenizing antimony selenium sulfide film as claimed in step (2) of claim 6, characterized in that: The steps include: (1) Cleaning of three-necked round-bottom flask, construction of condensation reflux device and nitrogen pipeline; (2) Weighing selenium powder and octadecene solution, placing them in a three-necked round-bottom flask with a stirrer, and adding a certain amount of ultrapure water; (3) Place a three-necked round-bottom flask on a magnetic stirring heating mantle and connect it to a condensing reflux device and a nitrogen pipeline; (4) setting the magnetic stirring heating mantle to an appropriate stirring speed, heating, introducing nitrogen, and carrying out the reaction under nitrogen protection; (5) After the reaction in step (4) is completed, the transparent solution is transferred to a star-shaped bottle and sealed to store in a dark place; (6) Filtering the solution after the growth in step (5) to obtain a post-selenization selenium source. (7) The post-selenization selenium source obtained in step (6) was spin-coated on the surface of the antimony selenide sulfide film at a rotation speed (3000 rpm / 30 s), and then the film was placed in a nitrogen-filled glove box for heat treatment at 350° C. for 10 min.

8. Use of the photovoltaic device as claimed in claim 3 in solar cells.

9. Use of the method for post-selenization of antimony selenium sulfide thin film as claimed in claim 7 in improving the efficiency performance of photovoltaic devices.